Pengaruh Gratis Ongkir, Online Customer Review dan Harga terhadap Keputusan Pembelian pada Platform Online Marketplace dengan Trust Sebagai Mediasi - Yuswardi; Rena (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the influence of free shipping, online customer reviews and price on purchasing decisions on online marketplace platforms with trust as mediation. In this research, the concept used in the research used is quantitative research. Quantitative research procedures are research where the results are presented in the form of descriptions using numbers and statistics. Quantitative research methodology is a scientific method for obtaining valid information with the aim of being able to create, confirm and improve insight so that it can in turn be used to master, uncover and estimate problems in specific aspects. The findings in this research are that each independent variable on purchasing decisions at Lazada and Shopee among Batam students has a positive and significant effect, except for the price variable. Meanwhile, if you look at the results of the indirect effect test, there are two variables whose results are not significant, namely the free shipping and promotion variables. However, from the hypothesis it can be found that the trust variable can mediate certain factors related to purchasing decisions in the Batam online market.